Laparoscopic Surgery for Acute Appendicitis Complicated by Peritonitis - O. V. Galimov; V. O. Khanov; D. M. Minigalin; D. O. Galimov; A. G. Safargalina; D. F. Galiullin (Креативная хирургия и онкология)
Introduction. Acute appendicitis (AA) is one of the most common acute abdominal surgical diseases. The current incidence, according to various authors, is 22.8 per 10,000 inhabitants. Annually, 50 to 70 thousand people die from AA and its complications around the world. Laparoscopy is generally accepted as the most effective method of differential diagnosis of AA. It is fundamentally significant to move from the diagnostic stage to the therapeutic one, i.e. to perform the elimination of the disease, including cases with other surgery-requiring pathology detected. Aim. To evaluate the role of video-endoscopic surgical methods in the surgical management of acute appendicitis complicated by peritonitis. Materials and methods. The analysis of recent publications and personal clinical experience revealed that diagnostic laparoscopy, unless contraindicated, should be performed as the initial step in suspected acute abdominal pathology. When the surgery is technically performable, laparoscopy also causes curative effect. Results and discussion. The use of laparoscopy in surgical treatment of acute appendicitis complicated by peritonitis has proven advantages for the patient over open surgery. An adequate appendectomy as a reliable method for elimination of the source of peritonitis is the key to successful treatment of patients. Laparoscopic lavage in the early postoperative period against the postoperative peritonitis with developing complications, is considered to be an alternative method to non-surgical treatment or delayed intervention and to have better ultimate results than percutaneous drainage or relaparotomy. Conclusion. The success of video-endoscopic technologies application depends not only on the technical aspects, but also on the correct choice of indications for such an intervention and their appropriate combination with open surgeries.